Semliki forest virus as a vector: Pros and cons for its use in biopharmaceuticals production - Núñez, Eutimio Gustavo Fernández [UNESP]; Jorge, Soraia Attie Calil; Astray, Renato Mancini; de Rezende, Alexandre Gonçalves; da Costa, Bruno Labate Vale; Monteiro, Daniella Cristina Ventini; Pereira, Carlos Augusto; Tonso, Aldo (FapUNIFESP (SciELO), 2013)
The number of biopharmaceuticals for medical and veterinarian use produced in mammalian cells is increasing year after year. All of them are obtained by stable recombinant cell lines. However, it is recognized that transient gene expression produces high level expression in a short time. In that sense, viral vectors have been extensively used for producing recombinant proteins on lab-scale. Among them, Semliki Forest virus is commonly employed for this purpose. This review discusses the main aspects related to the use of Semliki Forest virus technology as well as its advantages and drawbacks which limit currently its utilization in biopharmaceutical industry on large-scale.
Keywords: BHK-21; Large-scale bioprocesses; Mammalian cells; Recombinant proteins; SFV; Transient expression